The Impact of Work-Life Balance and Workload on Employee Performance at PT PLN (Persero) Customer Service Implementation Unit (UP3) Binjai - Fadhlal Nugraha; Hasrul Azwar Hasibuan; Saimara A.M Sebayang (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is the backbone of organizational success in public service institutions, including PT PLN (Persero) UP3 Binjai. This study aims to analyze the effect of work-life balance and workload on employee performance, both partially and simultaneously. A causal associative quantitative approach was employed, with data collected through a Likert-scale questionnaire ranging from 1 to 5. A total of 58 respondents were selected from 136 employees using Slovin's formula at a 10% margin of error. Data were analyzed using multiple linear regression with SPSS version 26. The results indicate that work-life balance has a positive and significant effect on employee performance, evidenced by a t-value of 15.918 with a significance level of 0.000. Meanwhile, workload shows no significant partial effect on performance, with a regression coefficient of +0.074, suggesting that employees have sufficiently adapted to existing work pressures. Simultaneously, both variables significantly influence employee performance, with an Adjusted R Square of 0.949, meaning 94.9% of performance variation is explained by the two variables. These findings confirm that maintaining a healthy balance between professional and personal life is the dominant factor driving employee productivity in the electricity service sector.